2013
DOI: 10.1016/j.jpainsymman.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Effects of Cancer Cachexia: A Systematic Literature Search and Qualitative Analysis

Abstract: The concept of psychosocial effects in cancer cachexia has the potential to sensitize health care professionals to cachexia-related problems and inform their clinical management of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 41 publications
2
94
0
9
Order By: Relevance
“…If the patient has entered a stage of refractory cachexia, the response to dietary treatment is no longer anticipated due to very advanced or rapidly progressive cancer unresponsive to anti-cancer therapy [2]. Even if nutritional or dietary treatment do not influence weight loss or survival it may be highly significant when it comes to eating-and weight loss-related distress, relief of certain symptoms, quality of life and social meaningfulness for the patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…If the patient has entered a stage of refractory cachexia, the response to dietary treatment is no longer anticipated due to very advanced or rapidly progressive cancer unresponsive to anti-cancer therapy [2]. Even if nutritional or dietary treatment do not influence weight loss or survival it may be highly significant when it comes to eating-and weight loss-related distress, relief of certain symptoms, quality of life and social meaningfulness for the patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A concern about one's look to family and friends was an additional source of worry. Oberholzer and colleagues also identified that some patients reported being embarrassed, not only because they worried about looking unhealthy, but because it resulted in increased pressure and reprimanding from their family to improve their nutritional intake when weight maintenance was not achieved [25]. In this study, patients with weight loss also reported being worried about the associated loss of energy.…”
Section: Discussionmentioning
confidence: 61%
“…A recent systematic literature review led by Oberholzer and colleagues identified the most prevalent psychosocial impacts of cancer cachexia, that resulted in sadness, disappointment, bewilderment, confusion, bother, concern, dissatisfaction, feeling upset, anger, frustration, guilt, desperation, anguish, fear, anxiety, and existential distress [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Involuntary weight loss, a main symptom of cancer cachexia, often follows anorexia and declining food intake, and thus these are causes of distress for patients. [1][2][3] Involuntary weight loss links to the deterioration of performance status, quality of life (QoL), nutritional status, treatment outcomes, and survival in advanced cancer patients.…”
Section: Introductionmentioning
confidence: 99%